2010
DOI: 10.1192/bjp.bp.109.075762
|View full text |Cite
|
Sign up to set email alerts
|

Help-seeking and receipt of treatment among UK service personnel

Abstract: BackgroundFor armed forces personnel, data on help-seeking behaviour and receipt of treatment for mental disorders are important for both research and policy.AimsTo examine mental healthcare service use and receipt of treatment in a sample of the UK military.MethodParticipants were drawn from an existing UK military health cohort. The sample was stratified by reserve status and by participation in the main war-fighting period of the Iraq War. Participants completed a telephone-based structured diagnostic inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 41 publications
7
88
1
1
Order By: Relevance
“…And some data indicate that military personnel are at higher risk of developing PTSD after a latent period with few symptoms than persons in other settings (72). Soldiers and other hierarchical professional groups may be reluctant to report symptoms until they become severe because of their fears of a negative impact on career and/or negative responses from their peers (72).…”
Section: Professionals Versus Civiliansmentioning
confidence: 99%
“…And some data indicate that military personnel are at higher risk of developing PTSD after a latent period with few symptoms than persons in other settings (72). Soldiers and other hierarchical professional groups may be reluctant to report symptoms until they become severe because of their fears of a negative impact on career and/or negative responses from their peers (72).…”
Section: Professionals Versus Civiliansmentioning
confidence: 99%
“…20 The average time from leaving service to MAP attendance was 12 years, similar to civilians. 49 Engagement with service was hampered for some by real or imagined guilt or shame at acts of omission or commission and remembrance of dead comrades.…”
Section: Help-seekingmentioning
confidence: 83%
“…14,15,20 Unlike the self-selecting MAP cohort, these studies have the benefit of being random samples on defined cohorts. Where there are data from the King's 2005 study 14 they are included for interest and comparison in the tables.…”
Section: Methodsmentioning
confidence: 99%
“…However, analyses comparing still serving military personnel and the general working population observed that military personnel were twice as likely to report common mental health difficulties (Goodwin et al, 2015). Further, veterans have been shown to have experienced higher levels of both childhood adversity and trauma in adulthood than nonveterans (Woodhead et al, 2011 • This is the first study of its kind in the UK to explore referral patterns for mental health difficulties in UK veterans at a national level • Over the last 20 years there has been nearly a fourfold increase in the numbers of veterans seeking support from a UK national mental health charity • In recent years the sharpest increase in demand has come from veterans who had deployed to Iraq and Afghanistan • Veterans from Iraq and Afghanistan are seeking help sooner than their colleagues who had deployed to previous conflicts personnel, less is known about the rates of help-seeking for mental health difficulties within veteran populations Iversen et al, 2010). Differences in prevalence rates of mental health difficulties between help-seeking veterans and the wider veteran population have been noted.…”
Section: What Is Known?mentioning
confidence: 99%